An Engel Curve for Variety - Li, Nicholas (The Review of Economics and Statistics, 2021)
I examine the source and welfare implications of differences in household consumption diversity. I document the existence of a positive correlation between household variety and expenditure to motivate a simple framework where households purchase more varieties to counteract diminishing returns to quantity but face location-specific costs of accessing variety. Estimating the model with Indian household data, I find that the increase in dietary diversity between 1983 and 2009 was mostly due to lower costs of accessing variety, which resulted in large welfare gains. Urban households also benefit from a lower cost of accessing varieties than rural households.